To Identify Myocardial Changes in Severely Malnourished Children: A Prospective Observational Study - Kumar, Neeraj; Pandita, Aakash; Sharma, Deepak; Kumari, Anita; Pawar, Smita; Digra, Kishour Kumar (Frontiers in Pediatrics, 2015)
Aim and objective The main purpose of this study is to identify the myocardial changes in severely malnourished children. Materials and methods This prospective, observational study, conducted for a period of 1 year, enrolled 200 children (120 males and 80 females) between 6 months and 5 years of age with severe protein–energy malnutrition, according to the criteria of the World Health Organization. The parents were duly informed, the study was explained and written consent was obtained. A random selection of cases was carried out, and they were further divided into five groups according to their age as follows: <1, 1–2, 2–3, 3–4, and 4–5 years. Electrocardiograms (ECGs) were taken at the time of admission for all the cases and the control group and were taken again after nutritional therapy either at the time of discharge or after a fortnight. The differences were then compared. Results On admission, 32% of cases had flat P-wave, out of which 75% reverted to normal with therapy. Similarly, 84% of cases had increased corrected QT interval at the time of admission. ST segment was depressed only in 8% of cases. 88% of cases had altered (flat to depressed) T wave at the time of admission. With the help of nutritional supplementation, all these abnormalities were back to a normal level at the time of discharge. Conclusion Electrocardiographic changes may be of help in assessing the severity and prognosis of severe acute malnutrition. The reversibility of ECG changes with dietary treatment suggests that the cardiac changes are not permanent in nature and may not affect adult life if the malnutrition is corrected. The cardiac status as denoted by heart rate remained the same even after a fortnight, suggesting that prolonged therapy and assessment of cardiac status is warranted even after fortnight therapy.